Pengaruh Latihan Kekuatan Lengan menggunakan Hand Paddles terhadap Kecepatan Renang 50 m Gaya Bebas - Alfi Nursal Fajri; Usman Wahyudi; Achmad Masfi (Journal of Sport Coaching and Physical Education, 2024)
In this study, it was found that crawl or freestyle swimming is a style often followed in competitions, but when doing the crawl swimming technique, the researcher found that the average arm strength of Jasalindo swimming athletes was still weak so that the arm strokes were not optimal, becoming one of the factors influencing the speed of the 50-m crawl swimming style. This study is because Jasalindo sport athletes are beginner athletes and there has been no research conducted at Jasalindo sport. This study seeks the effect of arm strength training using Hand Paddle on the speed of the 50-m crawl swimming style in Jasalindo club athletes. The method used is an Experiment with a Quasi Experimental design. With a sample of 40 athletes divided into two groups, namely the treatment group and the control group. The results obtained from the Normality Test and Paired T Test were analyzed. The Normality Test showed significant T test results when comparing the Pretest and Posttest scores of the experimental class, with a significance value of 0.00 <0.01. Thus H0 is rejected and H1 is accepted. The T test of the Pretest and Posttest values ​​in the experimental class also produced a significance value of 0.00 <0.01 so that H0 was rejected and H1 was accepted. Therefore, it can be concluded that Hand Paddles training has a positive effect on the speed of the 50 ms crawl swimming style.